A COMPARISON OF THE FCI SCORES OF AFGHAN AND MALAYSIAN STUDENTS WITH OTHER COUNTRIES - Abdul Manan Hairan; Gul Mohammad Azimi; Wali Mohammad Azizi; Saeedullah Sajjad (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This article focused on the comparison of the performances of Afghan, Malaysian university students and the results of students from other countries using the Force Concept Inventory (FCI). There were 90 Afghan and 70 Malaysian university students who participated in this study. The collected data were analysed using SPSS v. 24 and Microsoft Excel. The results of this investigation showed that generally, Afghan and Malaysian students had low level of conceptual understanding of Newtonian mechanics which is less than the Newtonian entry threshold for FCI. The results showed that there is a significant difference between Afghan and Malaysian university students in the level of conceptual understanding, where the mean score of Malaysian students is 9 percent higher than that of Afghan students. The results further showed that the average score of Afghan is lower than the average scores of students from other countries such as USA, China, UK, Russia, Finland, South Africa, Turkey, Saudi Arabia, Thailand, India, Indonesia and Malaysia. However, the Afghan results is slightly better than the Laos students’ results. The mean FCI score of the Malaysian students is about the same range of students mean FCI scores from some countries such as Africa, Thailand, Indonesia, Philippines, India, Turkey and Saudi Arabia. Finally, recommendations are made to improve students conceptual understanding in Introductory Physics as well as for further researches.